Ecorestoration of the coalmine degraded lands - Maiti, Subodh Kumar. (Springer India : Imprint: Springer, 2013)
The book adopts an application-oriented approach for ecorestoration of coalmine degraded. The theoretical aspects of ecorestoration, and steps involved in ecorestoration process and experimental aspects of thorough analytical procedures have been discussed in detail. It emphasizes on the types of mining, land degradation, and biodiversity conservation while giving details of technical and biological steps, topsoil management, selection of plant species, seeding, nursery practices; adoption of innovative approaches like mulching, biofertlizer application, hydroseeding, superabsorbent; use of grass-legume mix; monitoring and aftercare of reclaimed sites; the indicators of sustainable ecorestoration; and Rules and Acts implemented and followed across the world. Rest of the text to be uploaded with the manuscript as this box has limitiations.